Estudio de las cadenas operativas y la tecnología de la cerámica relacionada al sitio arqueológico Hacienda Tuncahúan, Catón Guano. - Rios Segovia, Ariel Marcelo (2024)
The current archaeological investigation entitled "Operational chains and ceramic technology related to the archaeological site Hacienda Tuncahúan" offers a detailed view of ceramic technology and its cultural significance in the Puruhá culture. Through an exhaustive analysis of ceramic fragments, diverse forms, techniques, and styles that reflect the skill of local potters were identified. The methodology used was quantitative, with a descriptive and exploratory research design. The researcher carried out a morphological, typological, and mineralogical analysis to study the composition of the ceramics. In addition, the empirical inductive method was applied to understand the origin, production, use, and meaning of the ceramics found at the site. The ceramics unearthed not only served practical purposes but also served as potent symbols of cultural identity and community unity, reflecting the ornamental and ceremonial practices of the Puruhá culture. The evolution in forms and styles observed points to a technical and artistic progression influenced by cultural and social shifts. The findings hint at a complex interplay between technical skills, cultural traditions, the natural environment, and the potential importation of raw materials, suggesting the existence of a robust commercial exchange network. The pivotal discovery of this research is the unveiling of the technical skills and cultural knowledge of the Puruhá potters, significantly enriching our understanding of the community's daily life, cultural practices, and artistic heritage through the in-depth analysis of the ceramic technology at Hacienda Tuncahúan.